Nonalcoholic Fatty Liver Disease - An Update 2019
DOI: 10.5772/intechopen.81474
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Bile Acids in Patients with NAFLD

Abstract: Bile acids are synthesized in the liver and tightly regulated through the enterohepatic circulation. Recent studies reveal that bile acids serve as hormone-like signaling molecules to activate nuclear receptors, notably farnesoid X receptor (FXR), regulating metabolic homeostasis of bile acids, cholesterol, lipids, and glucose. A connection between bile acids and nonalcoholic fatty liver disease (NAFLD) has long been recognized. Although inconsistent or even contradictory results are reported, a large body of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 142 publications
(247 reference statements)
2
21
0
Order By: Relevance
“…In healthy liver, BA metabolism is tightly regulated through enterohepatic circulation of BAs, and BA homeostasis is maintained through multiple negative feedback mechanisms, such as farnesoid X receptor (FXR)/small heterodimer partner (SHP) and FGF19/FGF receptor‐4 (FGFR4) signalling 37,38 . A growing body of literature has reported that the levels of total and primary BAs are elevated in the serum, plasma, stool and liver of patients with NAFLD, implying an association between BA metabolism and the pathogenesis of NASH 1,7 .…”
Section: Discussionmentioning
confidence: 99%
“…In healthy liver, BA metabolism is tightly regulated through enterohepatic circulation of BAs, and BA homeostasis is maintained through multiple negative feedback mechanisms, such as farnesoid X receptor (FXR)/small heterodimer partner (SHP) and FGF19/FGF receptor‐4 (FGFR4) signalling 37,38 . A growing body of literature has reported that the levels of total and primary BAs are elevated in the serum, plasma, stool and liver of patients with NAFLD, implying an association between BA metabolism and the pathogenesis of NASH 1,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is plausible that enhancement of cAMP signaling may potentiate BMP signaling pathway to potentiate GLP-1 secretion. It has also been reported that dysregulation of bile acid signaling became worse in patients with non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) [32]. Moreover, NAFLD and NASH patients have been reported to have deficiency in glucose-stimulated GLP-1 secretion [33].…”
Section: Discussionmentioning
confidence: 99%
“…MRP3 contributes to the transport of biliary excretion and was shown to get upregulated in both expression and activity in NAFLD patients as well as animal models. 47,48 In mice with hepatic steatosis, the mRNA levels of MRP3 increased by 3.3fold, compared to wild-type animals. 49 Comparable to these results, we observed an increase of up-to 3.4-fold in MRP3 expression levels in rat primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%